Gas-phase and matrix-isolation photochemistry of methyl thioglycolate, CH3OC(O)CH2SH : Influence of the presence of molecular oxygen in the photochemical mechanisms - Bava, Yanina Belén (2017)
The photochemistry of methyl thioglycolate (MTG), CH3OC(O)CH2SH, in gas phase and in matrix isolation conditions was studied by means of FTIR spectroscopy, and the influence of the presence of molecular oxygen on the photochemical mechanisms was investigated. The UV–vis broad-band photolysis of MTG in gas phase originates CH3OC(O)CH3 and S8, while in matrix conditions the photoproducts are CH3OH, H2CS, and CO, interacting inside the matrix cage. The photolysis of MTG in the presence of O2 conducts to the formation of SO2, independent of the experimental conditions, being CH3OH, HC(O)OH, and CO the other photoproducts for the gas-phase photolysis, and H2CO, CH4, and CO2 for the experiments performed in Ar matrix conditions.